Salvianolic Acid A Has Anti-Osteoarthritis Effect In Vitro and In Vivo - Wu, Yifan; Wang, Zhanghong; Lin, Zeng; Fu, Xin; Zhan, Jingdi; Yu, Kehe (Frontiers in Pharmacology, 2020)
Osteoarthritis (OA) is a shared degenerative disease in middle-aged and elderly people, which seriously affects their quality of life. Anti-inflammatory and anti-apoptosis pharmacological effects of salvianolic acid A (SAA) have been shown in many studies. In this study, we were intended to explore the anti-inflammatory and anti-apoptotic effects of SAA in OA. We evaluated the expression of pro-inflammatory mediators and cartilage matrix catabolic enzymes in chondrocytes by ELISA, Griess reaction, immunofluorescence, and Western blot, which includes nitric oxide (NO), tumor necrosis factor-alpha (TNF-α), interleukin-6 ( IL-6), prostaglandin E2 (PGE2), inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), MMPs (MMP-3, MMP-13), and ADAMTS-5. Besides, Bax, Bcl-2, and cleaved caspase-3 were measured by Western blot methods. The results of this experiment in vitro showed that SAA not only inhibited the production of inflammatory mediators induced by IL-1β and the loss of cartilage matrix but also reduced the apoptosis of mouse chondrocytes induced by IL-1β. According to the results of immunofluorescence and Western blot, SAA inhibited the activation of the NF-κB pathway and MAPK pathway. The results of these in vitro experiments revealed for the first time that SAA down-regulated the production of inflammatory mediators and inhibited the apoptosis of mouse chondrocytes and the degradation of extracellular matrix (ECM), which may be attributed to the inhibition of the activation of NF-κB and MAPK signaling pathways. In vivo experiments, 45 mice were randomly divided among three groups (the sham group, OA group, and OA + SAA group). The results of animal experiments showed that SAA treatment for eight consecutive weeks inhibited further deterioration of OA. These results demonstrate that SAA plays an active therapeutic role in the development of OA.